Physiological behavior of rubber plants (Hevea brasilliensis) to different soil moisture conditions - Mislan, Rohaizad; Sulaiman, Zulkefly; Abdullah, Siti Nor Akmar; Ismail, Mohd Razi; Karim, Sarker Mohammad Rezaul; Abdul Wahab, Mohd Aswad; Noran, Aizat Shamin (Universiti Putra Malaysia Press, 2024)
Drought conditions can severely impact rubber (Hevea brasiliensis) plantations, leading to economic loss in Malaysia. The study aimed to assess the impact of varying soil moisture levels on the physiological characteristics of five latex timber clones (LTCs) of rubber, with the goal of identifying the most suitable clone for specific soil moisture conditions. These conditions include (1) field capacity, (2) 75% available water (AW), (3) 50% AW, (4) 25% AW, and (5) wilting point, with the ultimate objective of optimizing cultivation methods and fostering sustainable rubber production in Malaysia. The five clones under investigation include RRIM3001, RRIM2025, RRIM2001, RRIM928, and PB350. Leaf chlorophyll content, stomatal conductance, and net photosynthesis were measured 4 and 8 months after treatment (MAT). The findings indicated significant effects of moisture stress on various physiological attributes, including total chlorophyll content, relative chlorophyll content, stomatal conductance, and net photosynthesis rate. At 4 and 8 MATs, the clones subjected to field capacity exhibited the highest values for these physiological characteristics, followed by those exposed to 75% available water, with the lowest values observed at the wilting point. RRIM3001 consistently exhibited the highest total chlorophyll content, stomatal conductance, and net photosynthesis among the clones at both sampling dates. The highest net photosynthesis was observed in the RRIM3001 clone under field capacity conditions. Furthermore, a significant positive correlation was identified between total chlorophyll and relative chlorophyll contents, as well as between net photosynthesis and stomatal conductance. These findings carry practical implications for water management during the initial growth phase of rubber seedlings and for replanting initiatives in rubber plantations.